Examining the reliability and validity of adapted LASRS-2 in Chinese context using AMOS-SEM approach - Li Yanyan; Lay, Yoon Fah; Gao Tongtong; Li Lihua; Hou Xiujuan (Conscientia Beam, 2025)
This pilot study aimed to examine the reliability and validity of the Lakaev Academic Stress Response Scale-2 (LASRS-2) in the context of Chinese college students. 186 undergraduate students from Xinyang College, China were enlisted for this research. Confirmatory Factor Analysis (CFA) was used to analyze data using the Amos Structural Equation Modeling (AMOS-SEM) methodology. Factor loading and composite reliability (CR) were used to identify the reliability criteria. Moreover, the average variance extracted (AVE) was used as an index of convergent validity and the heterotrait-monotrait criterion (HTMT) as the index of discriminant validity. The research results showed that the adapted LASRS-2 has good reliability and validity indicators after minor modifications for Chinese college students. The adapted LASRS-2 can be used in the future related to research in the Chinese context. The adapted LASRS-2 can measure college students' academic stress response involving four domains (affective response, behavioral response, cognitive response, and physiological response).